Taxonomic microidentification and new diagnostic characters of the sea urchin Astropyga pulvinata (Diadematoida: Diadematidae) - Juárez-Espinoza, Pablo A.; Solís-Marín, Francisco Alonso; Arreguín-Espinosa, Roberto A. (Revista de Biología Tropical, 2015)
Astropyga pulvinata is a sea urchin of the family Diadematidae that have five pairs of series of blue iridescent spots on interambulacral zones, from in vivo observation of 20 individuals under stereo-microscope and Scanning Electron Microscope analysis identification, the pedicellariae, spicules, and calcareous rosettes. The pedicellariae of A. pulvinata have three valves and are of three types: claviform, present on ambulacres; tridentates present on peristome and triphyllous present all over the test except in interambulacral areas. So ophicephalous pedicellariae are not bounded with a calcareous stalk. Ten types of spicules were observed from different soft tissues: one type from the intestine; three from the anal membrane; and six from the peristome, two of them constitute new diagnostic characters. One of them having a bat-shaped form and the other one with a waning crescent shape. In vivo observations showed that the blue iridescent spots were present on interambulacral areas as group of 35 cells bounded, and that other smaller spots were present on the ambitus, composed by eight cells.